Deepwater Horizon - Berg, Peter, 1964-; Wahlberg, Mark, 1971-; Russell, Kurt; Malkovich, John; Jablonsky, Steve (Santa Monica, California : Lionsgate, 2017)
The story of the BP Deepwater Horizon explosion and oil spill, which took place in 2010.
Originally released as a motion picture in 2016.
Wide screen 1.85:1.
Features: The fury of the rig, Deepwater surveillance, Work like an American.
Cinematographer, Enrique Chediak ; production designer, Chris Seagers ; editors, Gabriel Fleming, Colby Parker, Jr. ; music, Steve Jablonsky.
Mark Wahlberg, Kurt Russell, John Malkovich, Gina Rodriguez, Dylan O'Brien.
MPAA rating: PG-13.
Keywords: BP Deepwater Horizon Explosion and Oil Spill, 2010 -- Drama; Deepwater Horizon (Drilling rig) -- Drama; Oil well drilling rigs -- Drama; Disaster films; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films